Patterns of Use and Relationships Between Digital Tools and Mathematics Learning Outcomes among Junior High School Students - Aziz, Saddam Al; Jupri, Al; Rani, Maulani Meutia (Jurnal Pendidikan Matematika, 2026)
Information and communication technology has expanded the availability of digital tools for mathematics learning; however, studies that simultaneously compare junior high school students' usage patterns of GeoGebra, Photomath, and ChatGPT and examine their relationships with mathematics learning outcomes remain limited. This study aimed to analyze the usage patterns of these three digital tools and examine the relationship between their use and students' mathematics learning outcomes. A non-experimental quantitative approach with a descriptive-correlational design was employed, supported by semi-structured interviews. The sample comprised 43 eighth-grade students from a public junior high school in Padang City, Indonesia, selected through purposive sampling. Data were collected through a Likert-scale questionnaire, midterm mathematics exam scores, and semi-structured interview guides, and were analyzed through descriptive statistics, normality tests, Kendall's tau-b, and Spearman's rho. Data analysis was conducted using nonparametric correlation tests, specifically Kendall's tau-b and Spearman's rho. The results showed that ChatGPT was the most frequently used tool, followed by Photomath, and GeoGebra was the least used. Interviews indicated that students considered ChatGPT more practical for obtaining explanations, while GeoGebra was less used because students were unfamiliar with its menus. Correlation analysis showed a moderate, significant positive relationship between digital tool use and midterm exam scores, with Kendall's tau-b = 0,421, p < 0,001, and Spearman's rho = 0,521, p < 0,001. These findings provide a preliminary indication that digital tool use may be associated with mathematics learning outcomes, while highlighting the need for structured teacher guidance in integrating digital tools pedagogically and ethically. Teknologi informasi dan komunikasi telah memperluas ketersediaan alat digital untuk pembelajaran matematika; namun, penelitian yang secara bersamaan membandingkan pola penggunaan GeoGebra, Photomath, dan ChatGPT oleh siswa sekolah menengah pertama serta mengkaji hubungannya dengan hasil belajar matematika masih terbatas. Penelitian ini bertujuan untuk menganalisis pola penggunaan ketiga alat digital tersebut dan mengkaji hubungan antara penggunaannya dengan hasil belajar matematika siswa. Pendekatan kuantitatif non-eksperimental dengan desain deskriptif-korelatif digunakan, didukung oleh wawancara semi-terstruktur. Sampel terdiri dari 43 siswa kelas delapan dari sebuah SMP negeri di Kota Padang, Indonesia, yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert, nilai ujian tengah semester matematika, dan panduan wawancara semi-terstruktur, serta dianalisis menggunakan statistik deskriptif, uji normalitas, Kendall’s tau-b, dan Spearman’s rho. Analisis data dilakukan menggunakan uji korelasi non-parametrik, yaitu Kendall’s tau-b dan Spearman’s rho. Hasil menunjukkan bahwa ChatGPT adalah alat yang paling sering digunakan, diikuti oleh Photomath, sedangkan GeoGebra adalah yang paling jarang digunakan. Wawancara menunjukkan bahwa siswa menganggap ChatGPT lebih praktis untuk mendapatkan penjelasan, sementara GeoGebra kurang digunakan karena siswa tidak familiar dengan menunya. Analisis korelasi menunjukkan hubungan positif dan signifikan dengan tingkat sedang antara penggunaan alat digital dan nilai ujian tengah semester, dengan Kendall’s tau-b = 0,421, p < 0,001, dan Spearman’s rho = 0,521, p < 0,001. Temuan ini memberikan indikasi awal bahwa penggunaan alat digital mungkin berhubungan dengan hasil belajar matematika, sekaligus menyoroti perlunya bimbingan guru yang terstruktur dalam mengintegrasikan alat digital secara pedagogis dan etis.